Application of intraoperative infrared thermography in bypass surgery for adult moyamoya syndrome: A preliminary study - Lin, Jinghui; Wu, Yiwen; Deng, Xinpeng; Zhou, Shengjun; Liu, Yuchun; Zhang, Junjun; Zeng, Yiyong; Li, Xianru; Gao, Xiang; Xu, Bin; Zhou, Chenhui (Frontiers in Neurology, 2023)
Background and objectives Cerebral revascularization surgery is the mainstay of treatment for moyamoya syndrome (MMS) today, and intraoperative determination of the patency of the revascularized vessel is a critical factor in the success of the procedure. Currently, major imaging modalities include intraoperative indocyanine green (ICG) videoangiography (ICG-VA), digital subtraction angiography (DSA), and vascular ultrasound Doppler. Infrared thermography is a modern imaging modality with non-contact devices for the acquisition and analysis of thermal data. We aimed to investigate the feasibility and advantages of infrared thermography in determining anastomotic patency during MMS surgery. Methods Indocyanine green videoangiography and infrared thermography were performed simultaneously in 21 patients with MMS who underwent bypass surgery. The detection result of vessel patency was compared, and the feasibility and advantages of infrared thermography were assessed. Results The patency of the anastomosis was accurately determined in 21 patients using either ICG angiography or infrared thermography. In 20 patients, the results of infrared thermography showed that the vascular anastomosis was unobstructed, and there was an agreement with the subsequent results of ICG-VA. In one patient, we suspected inadequate patency after testing the anastomosis with infrared thermography, and the results of ICG-VA evaluation of the anastomosis confirmed that there was indeed an anastomotic obstruction. Conclusion Compared with ICG-VA, infrared thermography might offer an alternative non-invasive, contrast-free option in assessing anastomosis patency compared with ICG-VA, and it is likely to become more widely used in the clinic in the near future.